Quality Of Life Assessment For Patients And Families With Primary Immunodeficiency In Malaysia - Meelad, Ruwaydah Ahmed Mohammed (2022)
Primary immunodeficiency disease (PID) affects various aspects of a patient’s life. However, the health-related quality of life (HRQOL) is poorly defined in Malaysian PID patients. Using a two-phase methodology, this study aimed to determine the quality of life of Malaysian PID patients and parents. The first phase was a quantitative study involving the assessment of the quality of life using the PedsQL Malay version (4.0) questionnaire. This cross-sectional study was performed from August 2020 to November 2020. Patients with PID and their families were invited to answer the PedsQL Malay version (4.0) questionnaire: a tool used to assess the HRQOL. The data were compared with previously published values of healthy Malaysian children. The second phase of the study involved qualitative interviews meeting with 10 parents through an audio recording at PID clinic (IPPT hospital), which was conducted from 1st of March to 30th May 2021. The interviews lasted for approximately 30 minutes with each parent, and the records were transcribed and translated from Malay to the English language. Subsequently, thematic analysis via ATLAS. ti version 9 was performed. A total of 41 families and 33 PID patients completed the questionnaire (the first phase of the study). Respondents’ parents recorded a lower mean total score than those of normal healthy children (67.26±16.73 vs. 79.51±11.90, p = 0.001, respectively). PID patients reported lower mean total score to normal healthy children (73.68 ± 16.38 vs. 79.51 ± 11.90, p = 0.04), including psychosocial domain (71.67±16.82 vs. 77.58±12.63, p = 0.05), and school functioning, (63.94±20.87 vs. 80.00 ±14.40, p = 0.007).